Perception de la gestion du paysage - Martin Coy; Norbert Weixlbaumer (Revue de Géographie Alpine)
Complex landscape management instruments based on a dynamic, innovative land-conservation paradigm and spatial zoning to provide for graded intensity of protection and human use are being implemented in the newer generation of biosphere reserves and biosphere parks. The multifunctionality of these exemplary landscapes with sustainable development is a great challenge; it also offers considerable potential for conflict. This paper intends to demonstrate the extent to which multifunctionality has been realised in the alpine Großes Walsertal Biosphere Park, and how the local population perceive the quality of their park five years after it was created. Landscape management efforts in the Großes Walsertal were monitored by accompanying regional-economic and perceptional studies, resulting in a discussion of required future actions.